2020
DOI: 10.3390/su12208518
|View full text |Cite
|
Sign up to set email alerts
|

Gender-Typed Sport Practice, Physical Self-Perceptions, and Performance-Related Emotions in Adolescent Girls

Abstract: Youth sport experience provides opportunities for physical, personal, and social development in youngsters. Sport is a social system in which socially constructed gender differences and stereotypes are incorporated, and specific sport activities are often perceived as gender characterized. The objective of this study was to examine the relationship between some salient physical and emotional self-perceptions and the type of sport practiced. A sample of 261 female athletes, aged 14–21 years (Mage = 15.59, SD = … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
11
0
8

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2
1

Relationship

4
4

Authors

Journals

citations
Cited by 18 publications
(21 citation statements)
references
References 64 publications
2
11
0
8
Order By: Relevance
“…At the end of the intervention program, the BMI average in the EG was considerably improved, whereas, in the CG, it remained stable or even increased. These findings are consistent with previous studies that demonstrate an association between body weight, self-efficacy, and aerobic physical activity exists ( Trost et al, 2001 ; Ievers-Landis et al, 2019 ; Morano et al, 2020 ). The results of these studies support the hypothesis that moderate-to-vigorous aerobic exercise activity is more effective than low-intensity exercise in inducing weight loss ( Keane et al, 2017 ).…”
Section: Discussionsupporting
confidence: 93%
“…At the end of the intervention program, the BMI average in the EG was considerably improved, whereas, in the CG, it remained stable or even increased. These findings are consistent with previous studies that demonstrate an association between body weight, self-efficacy, and aerobic physical activity exists ( Trost et al, 2001 ; Ievers-Landis et al, 2019 ; Morano et al, 2020 ). The results of these studies support the hypothesis that moderate-to-vigorous aerobic exercise activity is more effective than low-intensity exercise in inducing weight loss ( Keane et al, 2017 ).…”
Section: Discussionsupporting
confidence: 93%
“…Netball is usually perceived as a feminine sport (Sobal & Milgrim, 2019) or a women's game (Broomhall, 1994). According to Metheny's (1965) categories, Gymnastics was one of the permissible sports for girls and defined as a female-appropriate sport (Morano et al, 2020;Riemer & Visio, 2003), or as simply a feminine sport (Plaza et al, 2017;Sobal & Milgrim, 2019). Moreover, the UK's sports with the second-highest number of female board members, Dance and Horse-riding, are mostly associated with the female gender by the literature (Plaza et al, 2017;Sobal & Milgrim, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…The general results of the study highlight that female gender-typed sports do not in themselves have the ability to promote a better position for women in their governance unless somehow supported by gender quotas. Literature focused on the sex-typing of sports showed that gender division in sports tended to resist through time and gender policies adopted at the national or European level (Klomsten et al, 2005;Morano et al, 2020;Plaza et al, 2017) Specifically, some types of sports such as Danc-ing and Gymnastics are traditionally considered to be related to hegemonic femininity (Plaza et al, 2017;Sobal & Milgrim, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Sport involvement offers young people the opportunity to learn and develop numerous physical skills and abilities, which in turn enhance their physical self-perceptions. Indeed, research findings in children and adolescents have consistently shown organized sports participation to be positively related to physical self-concept ( Balaguer et al, 2012 ; Amado-Alonso et al, 2018 ; Morano et al, 2020b ), self-esteem, and sport competence ( Rubeli et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%